Subunit vaccines for Acinetobacter baumannii - Yang, Ning; Jin, Xiao; Zhu, Chenghua; Gao, Fenglin; Weng, Zheqi; Du, Xingran; Feng, Ganzhu (Frontiers in Immunology, 2023)
Acinetobacter baumannii is a gram-negative bacterium and a crucial opportunistic pathogen in hospitals. A. baumannii infection has become a challenging problem in clinical practice due to the increasing number of multidrug-resistant strains and their prevalence worldwide. Vaccines are effective tools to prevent and control A. baumannii infection. Many researchers are studying subunit vaccines against A. baumannii. Subunit vaccines have the advantages of high purity, safety, and stability, ease of production, and highly targeted induced immune responses. To date, no A. baumannii subunit vaccine candidate has entered clinical trials. This may be related to the easy degradation of subunit vaccines in vivo and weak immunogenicity. Using adjuvants or delivery vehicles to prepare subunit vaccines can slow down degradation and improve immunogenicity. The common immunization routes include intramuscular injection, subcutaneous injection, intraperitoneal injection and mucosal vaccination. The appropriate immunization method can also enhance the immune effect of subunit vaccines. Therefore, selecting an appropriate adjuvant and immunization method is essential for subunit vaccine research. This review summarizes the past exploration of A. baumannii subunit vaccines, hoping to guide current and future research on these vaccines.